Fundamental of Entrepreneurship ENT300 : Lesung Bonda Restaurant / Nur Aqmar Syahmina Ramian ... [et al.] - Ramian, Nur Aqmar Syahmina; Hassan, Nur Hasya' Shazwani; Hamdan, Nurhasfazera; Bujang, Nurfaziela (UiTM Cawangan Sarawak, 2016)
The business plan af Lesung Boruda is proposed so that it can be taken by comprehensive manner. This business plan gives opportunity for us to access business in the future. The business is i9n from of enterprise which consists of four shareholders. All shareholders had agreed as stated in the agreement letter than mentioned about capital, contributions, loss and profit of the business. We choose this business because it shows the equality and no one will decimated as the profit and loss will be divided as stated ratio and the financial manager will announce whether the business will gain how much profits or losses by the end of the year sales.